Clinical Profile and In-Hospital Outcome of COVID-19 Infection among Patients with Cardiovascular Disease: A Cross-Sectional Study - Ghimire, Roshan; Gajurel, Ratna M; Paudel, Chandra M; Shrestha, Hemant; Khanal, Rajaram; Manandhar, Bhawani; Shakya, Smriti; Shakya, Samir; Yadav, Vijay; Sharma, Manju; Yadav, Sutap; Shah, Nischal; et al. (Journal of Institute of Medicine Nepal, 2022)
Introduction Coronary heart disease, hypertension, heart failure, diabetes, and other cardiovascular diseases (CVD) increase the disease severity and in-hospital mortality among patients with COVID-19. Methods This is a hospital-based study assessing the effects of CVD on the in-hospital outcomes in patients admitted with COVID-19. Clinical characteristics and in-hospital outcomes were studied in patients with cardiovascular risk factors and underlying CVD. Results A total of 108 covid positive patients had an underlying cardiovascular disease/s in various forms with a mean age of 60.69±16.24 years and 55.6% were male. Hypertension and diabetes mellitus were the commonest cardiovascular risk factors. Among these patients, acute decompensated heart failure and cardiac arrhythmia commonly atrial fibrillation were the common cardiac complications. The in-hospital mortality rate was 16.67%. Those who died due to cardiac involvement was 18.2% in comparison to 14.3% of the patients who did not have cardiac involvement, although this could not reach statistical significance. The most common cause of death was multiorgan failure resulting in 44.45 % of all cause of death followed by acute respiratory distress syndrome accounting 27.78 % and refractory cardiogenic shock with 22.22 % involvement. Among those who died vs those who survived length of hospital stay was significantly longer in death group (13.6 days vs 9.11 days, P=0.002) Conclusion In patients hospitalized with COVID-19, pre-existing established cardiovascular risk factors and CVD appear to be important contributors to mortality. The involvement of multiorgan predisposes COVID-19 patients to accentuated risk of mortality.